The Canterville ghost - Wilde, Oscar, 1854-1900.; Moore, Inga (Cambridge, Mass. : Candlewick Press, 1997)
A celebrated and feared English ghost is outraged when the new American owners of his haunting place refuse to take him seriously and actually fight back against him.
Keywords: Ghosts -- Fiction; England -- Fiction